The Provision of Non-Audit Services, Audit Fees and Auditor Independence - Ayoib Che Ahmad,; Rohami Shafie,; Nor Zalina Mohamad Yusof, (Asian Academy of Management Journal of Accounting and Finance, 2006)
The objectives of this study are to examine the effect of non-audit services on audit fees, to investigate the relationship between non-audit fees and the issuance of qualified audit opinion, and to analyse the proportion of non-audit fees to total fees paid by a client to its auditor. The regression analysis reveals a significant positive relationship between audit fees and non-audit fees, which is contrary to the theory available in the literature. Further tests are done and alternative explanations are provided. The results obtained from the t-test suggest a significant relationship between non-audit fees and qualified audit opinions. The outcomes indicate that on average audit opinions are dependent on the amount of non-audit fees. Finally, the descriptive analysis presents a worrying development about the ratio of non-audit fees to total fees. The study suggests ways to improve the independence issues in Malaysia.